Role of Accountant to Net Zero Emission Carbon in Power Plant Company PT. Cikarang Listrindo Tbk - Jarot, Haryanto; Pribadi D, Yanuar; Ariza, Dani; Sihalolo, S. Wolker; Ramadhan, Yanuar (Publikasi Indonesia, 2023)
The application of accounting towards zero carbon emissions in power generation companies is a strategic initiative in facing the challenges of global climate change. Power generation companies are increasingly realizing the importance of reducing their environmental impact by adopting sustainable practices. One of the key steps in achieving this goal is to implement accounting that focuses on measuring, reporting, and managing carbon emissions. The study examines power companies' efforts in implementing zero carbon emissions accounting as part of their sustainability strategy. The approach involved identifying, measuring, and reporting carbon emissions from companies' operations, energy resources, and supply chains. This data is then used to develop carbon emission reduction strategies and identify energy efficiency opportunities. The results of the study show that the implementation of zero carbon emission accounting has helped power generation companies to identify potential carbon emission reductions, improve their operational efficiency, reduce environmental impact, and support business continuity. In addition, public disclosures about carbon emissions have strengthened the company's image in the eyes of stakeholders, such as customers, investors, and regulators.